Toxicity of arsenite to earthworms and subsequent effects on soil properties. (February 2018) - Wang, Yali; Wu, Yizhao; Cavanagh, Jo; Yiming, Ayizekeranmu; Wang, Xiuhong; Gao, Wen; Matthew, Cory; Qiu, Jiangping; Li, Yinsheng
Abstract: Arsenic (As) is widely distributed in soil and is toxic to plants, animals and humans. In this study, earthworms ( Eisenia fetida ) were exposed to five concentrations of sodium arsenite (5, 10, 20, 40, and 80 mg As kg −1 ) in farm soils for 28 d. With increasing soil As(III) concentrations, As bioaccumulation in earthworms increased (maximum bioaccumulation factor 3.77), and levels of reactive oxygen species (ROS) and malondialdehyde (MDA) were elevated. The expression of nuclear factor erythroid 2- related factor 2 (Nrf2) and heme oxygenase -1 (HO-1) were upregulated by As in a dose-dependent pattern, and reached 5.93 and 2.94 times the control values for Nrf2 and HO-1 respectively, at 28 d in the 80 mg As kg −1 soil treatment. Similarly, DNA damage, as measured in earthworm sperm using the comet assay, increased with increasing As(III) concentrations, with 'Olive tail moment' values in the comet assay ranging from c. 0.5 in Control to c. 3.5 at 80 mg As kg −1 soil. In contrast, activity of the antioxidant enzymes, superoxide dismutase (SOD) and catalase (CAT), decreased. These results indicate that As(III) caused oxidative stress that resulted in damage to lipids and DNA. Nrf2 and HO-1 protein expression was demonstrated in earthworms for the first time to our knowledge, and found to be a sensitive biomarker of arsenic contamination. The presence of earthworms was also found to change the distribution of As in soil, in particular, reducing the proportion in the residual fraction and increasing the proportion in As bound to Fe-oxides. This may result in increased bioavailability of bound arsenic. Soil organic matter, NH4 + -N, NO3 − -N and available K were indirectly changed by the As(III) through its toxicity to earthworms. This study helps to inform future assessments and biomonitoring of soil arsenic contamination. Highlights: Evidence of the Nrf2 and HO-1 signal pathway in earthworms. Nrf2 and HO-1 are sensitive biomarkers of arsenic exposure. Total As content rather than As fractions affected oxidative stress in earthworm. Arsenite caused DNA damage of earthworm sperm and correlated to oxidative stress. Soil nutrient properties was indirectly affected by toxicity of As(III) to earthworms.